Fallgirls: Gender and the Framing of Torture at Abu Ghraib (Classical and Contemporary Social Theory), by Ryan Ashley Caldwell - Pau Pérez Sales (Torture)
Initially published in 2012 and now reedited, this book constitutes a peculiar contribution to the torture literature on perpetrators. Existing books have already covered: self-justifying perspectives written by perpetrators (i.e. Aussaresses, 2010; Moore-King, 1998; Pardo, 2014; Troccoli, 1996); interviews with perpetrators or analysis from autobiographical texts (i.e. Conroy, 2000; Crelinsten & Schmid, Alex P (Eds.), 1995; Haritos-Fatouros, 2003; Payne, 2008; Pérez-Sales, 2017); and analysis of the interaction from a survivor’s viewpoint (Gil, 1999). There also exists a wealth of social psychology books that attempt to theorize the logic and dynamics of becoming a perpetrator (i.e. Bandura, Barbaranelli, Caprara, & Pastorelli, 1996; Browning, 1992; Miller, 2004; Staub, 1999). Caldwell’s book adopts the extreme hypothesis that the soldiers England and Harman, judged for acts of misconduct in Abu Ghraib after the leakage of dozens of terrible pictures, are innocent. The book goes on to defend the nearly untenable thesis that England and Harman must be considered victims themselves. It is thus wholly unsurprising to find out that Caldwell was part of the legal defence team for both soldiers.